Novel De Novo Heterozygous Variants in the SON Gene Causing ZTTK Syndrome: A Case Report of Two Patients and Review of Neurological Findings. (November 2022) - Eid, Maya; Bhatia, Sonal
Zhu-Tokita-Takenouchi-Kim (ZTTK) syndrome is a newly described autosomal dominant multisystem developmental disorder resulting from a mutation of the SON gene located on chromosome region 21q22.11. It is characterized by heterogeneous features such as intellectual disability, facial dysmorphisms, poor feeding, vision abnormalities, musculoskeletal anomalies, congenital heart and genitourinary system defects, as well as several unique neurological findings including seizures, tone abnormalities, autism spectrum disorder and variable brain abnormalities noted on neuroimaging. Unfortunately, we lack adequate information regarding the spectrum of these neurological symptoms. In this study, we report 2 new unrelated cases of ZTTK syndrome, and identify new pathogenic variants in the SON gene through microarray analysis and whole-exome sequencing. We also emphasize the neurological manifestations of the syndrome in our patients and discuss the significance of gathering more data regarding neurological presentation, particularly seizure characteristics and long-term developmental progression. This information will be crucial to help understand long-term neurodevelopmental prognosis in these patients.